Peran media video animasi interaktif berbasis canva dalam meningkatkan literasi digital siswa SD - Alfina Diniyati; Imas Mastoah (Universitas Sebelas Maret, 2025)
This study aims to investigate the function of an interactive animated video medium, specifically designed through Canva, in facilitating increased acquisition of digital literacy among primary school students. The educational landscape requires continuous evolution to ensure that pedagogical methodologies remain relevant and impactful in the face of rapid technological advancements. This question underscores the utilization of Canva as an accessible graphic design tool for the creation of captivating, visual and interactive educational media. The main methodology used in this study consisted of a literature review and qualitative descriptive analysis. Animated videos produced through Canva have the potential to simplify abstract concepts for students, thus enhancing their understanding of the material presented. The application of such media also fosters creativity, critical thinking skills and digital communication competencies, which are essential components of digital literacy. The research findings show that video media based on Canva significantly increases students' motivation and active engagement. Nevertheless, to achieve optimal implementation, it is crucial to ensure adequate infrastructure support, teacher readiness in technology proficiency, as well as proactive and responsible student participation in the digital learning experience.